Notch1 Deficiency Induces Tumor Cell Accumulation Inside the Bronchiolar Lumen and Increases TAZ Expression in an Autochthonous Kras LSL-G12V Driven Lung Cancer Mouse Model - Meder, Lydia; Florin, Alexandra; Ozretic, Luka; Nill, Marieke; Koker, Mirjam; Meemboor, Sonja; Radtke, Freddy; Diehl, Linda; Ullrich, Roland T.; Odenthal, Margarete; Buettner, Reinhard; Heukamp, Lukas C. (Pathology & Oncology Research, 2021)
Purpose: Abrogation of Notch signaling, which is pivotal for lung development and pulmonary epithelial cell fate decisions was shown to be involved in the aggressiveness and the differentiation of lung carcinomas. Additionally, the transcription factors YAP and TAZ which are involved in the Hippo pathway, were recently shown to be tightly linked with Notch signaling and to regulate the cell fate in epidermal stem cells. Thus, we aim to elucidate the effects of conditional Notch1 deficiency on carcinogenesis and TAZ expression in lung cancer. Methods: We investigated the effect of conditional Cre-recombinase mediated Notch1 knock-out on lung cancer cells in vivo using an autochthonous mouse model of lung adenocarcinomas driven by KrasLSL-G12V and comprehensive immunohistochemical analysis. In addition, we analyzed clinical samples and human lung cancer cell lines for TAZ expression and supported our findings by publicly available data from The Cancer Genome Atlas (TCGA). Results: In mice, we found induction of papillary adenocarcinomas and protrusions of tumor cells from the bronchiolar lining upon Notch1 deficiency. Moreover, the mutated Kras driven lung tumors with deleted Notch1 showed increased TAZ expression and focal nuclear translocation which was frequently observed in human pulmonary adenocarcinomas and squamous cell carcinomas of the lung, but not in small cell lung carcinomas. In addition, we used data from TCGA to show that putative inactivating NOTCH1 mutations co-occur with KRAS mutations and genomic amplifications in lung adenocarcinomas. Conclusion: Our in vivo study provides evidence that Notch1 deficiency in mutated Kras driven lung carcinomas contributes to lung carcinogenesis in a subgroup of patients by increasing TAZ expression who might benefit from TAZ signaling blockade.
CRIS-Team Scopus Importer:2023-03-21
Keywords: KRAS; lung cancer; mouse model; NOTCH1; TAZ